2020
DOI: 10.1111/oik.07074
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between winter and summer herbivory affect spatial and temporal plant nutrient dynamics in tundra grassland communities

Abstract: In the long‐term, herbivores can alter nutrient dynamics in terrestrial ecosystems by changing the functional composition of plant communities. Here, we ask to what extent herbivores can affect plant‐community nutrient dynamics in the short‐term. We provide theoretical expectations for immediate effects of herbivores on tundra‐grassland plant‐community nutrient levels throughout a single growing season and empirically evaluate these predictions. We established an experiment within two forb‐dominated and two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 60 publications
1
31
0
Order By: Relevance
“…Similarly, outbreaks of invertebrate herbivores can influence the livelihood of northern communities [5] through their dramatic impacts on vegetation and the subsequent cascading effects on local wildlife [6,7]. Herbivores also play an important ecological role in Arctic tundra ecosystems by influencing soils [8] and plant communities [9,10], with consequences for ecosystem processes [11]. Moreover, herbivores have the potential to offset some of the effects of ongoing warming in tundra ecosystems by counteracting increases in deciduous shrub cover [12,13] or advances of the treeline [14].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, outbreaks of invertebrate herbivores can influence the livelihood of northern communities [5] through their dramatic impacts on vegetation and the subsequent cascading effects on local wildlife [6,7]. Herbivores also play an important ecological role in Arctic tundra ecosystems by influencing soils [8] and plant communities [9,10], with consequences for ecosystem processes [11]. Moreover, herbivores have the potential to offset some of the effects of ongoing warming in tundra ecosystems by counteracting increases in deciduous shrub cover [12,13] or advances of the treeline [14].…”
Section: Introductionmentioning
confidence: 99%
“…This could be particularly relevant in high-latitude regions, such as the tundra, where herbivores have a short time-window to access plants and hence any changes in plant quality may have large consequences for their fitness (Beard et al, 2019;Doiron et al, 2015;White, 1983). We have recently shown that, within a single summer, mammalian herbivores enhance plant nutrient dynamics in tundra grasslands (Petit Bon, Inga, et al, 2020). Here, we ask to what extent herbivores modify the quality of tundra grasses by altering their Si-content in relation to their nitrogen (N) and phosphorus (P) levels.…”
Section: Introductionmentioning
confidence: 99%
“…During peak abundances, which can occur both in summer and winter, small rodents visibly disturb the vegetation (Hambäck et al, 1998;Ims & Fuglei, 2005). Such disturbance also represents a major pathway through which small rodents affect tundra plant-community nutrient levels (Petit Bon, Inga, et al, 2020;Tuomi et al, 2018). In contrast, Rangifer (reindeer/caribou) show largescale spatial dynamics through their migratory behaviour and their impacts by grazing and trampling on vegetation are more likely to be seasonal (Bernes et al, 2015;Tuomi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Given that vole and lemming populations experience population fluctuations across the Arctic 22 , rodent peaks should be important disturbance events in almost the entire biome. The slow growth rates of low productive Arctic vegetation 23 , result in the Arctic tundra being a mosaic of patches in different successional stages with implications for plant community composition and plant nutrient content 36 . Quantifying the heterogeneity of rodent impacts using UAVs makes it possible to estimate the importance of rodents on fundamental aspects of Arctic ecosystems, i.e.…”
Section: Introductionmentioning
confidence: 99%